(untitled) (Tamaddun, 2017)
PThis study aims to find variations in the language used by a group of people, especially the Ma- kassar language. The author is interested in finding several ways to apologize in the Makassar language in the context of different situations. The author uses semi-structural interviews in obtaining the data, and has interviewed 3 (three) people who work in the field of culture and history at the Lagaligo Museum in the South Sulawesi Archaeological Office. The data found has shown that it is interesting to know a number of ways to apologize in the Makassar language and in different situations, and integrated with language items, speech communities, language variations and standard languages. And the most prominent is the variety of languages used in apologizing such as visiting someone, eating and drinking, social interactions such as marriage, apologizing for an error, and others.